79.5k views
5 votes
Log(x+1)−log(x−8)=log(10)

How do i solve this?

User Dhruv Garg
by
5.3k points

1 Answer

6 votes

9514 1404 393

Answer:

x = 9

Explanation:

The applicable rule of logarithms is ...

log(a) -log(b) = log(a/b)

__

Use the rules of logarithms to simplify the left side to a single log, then take the antilogs and solve the resulting equation.

log(x+1) -log(x-8) = log(10)

log((x+1)/(x-8)) = log(10)

(x +1)/(x -8) = 10 . . . . . . . take antilogs

x +1 = 10(x -8) . . . . multiply by x-8

81 = 9x . . . . . . . add 81-x, simplify

9 = x . . . . . . . . . divide by 9

_____

When the equation is rewritten to the form f(x) = 0, the x-intercept is the solution.

Log(x+1)−log(x−8)=log(10) How do i solve this?-example-1
User VladacusB
by
5.7k points